Online onboarding program to strengthen the commitment and retention of employees of a private company in the city of Chimbote - Cardoza Sernaqué, Manuel Antonio (2022)
Conferencia en 2nd LACCEI International Multiconference on Entrepreneurship, Innovation and Regional Development - LEIRD 2022: “Exponential Technologies and Global Challenges: Moving toward a new culture of entrepreneurship and innovation for sustainable”, Virtual Edition.